2010
DOI: 10.3109/13880209.2010.501802
|View full text |Cite
|
Sign up to set email alerts
|

Plants used for the treatment of diabetes in Jordan: A review of scientific evidence

Abstract: Additional in vitro and in vivo studies are needed to test the hypoglycemic activity of the plants with claimed antidiabetic activity which has not yet been evaluated. Identification of the active ingredients of potent plants might generate lead compounds in drug discovery and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 111 publications
0
40
0
Order By: Relevance
“…[36] Hence the evidence for a candidate potent effect of folk herbal medicine occupy in dealing to anti-diabetes. [39] Moreover, the effectiveness of folk medicine must be herbal therapies as to build few adverse effects and reduce costly for alternative hyperglycemia agents. Particularly, curcumin (bis-α,β-unsaturated β-diketone), the chief constituent of turmeric plant (C. longa), plays a significant role in prevention of various diseases including diabetes by decrease blood glucose and increase plasma insulin level, [40] while different species has been taken as anti-diabetic agents in potent and safety on therapy of patient's diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…[36] Hence the evidence for a candidate potent effect of folk herbal medicine occupy in dealing to anti-diabetes. [39] Moreover, the effectiveness of folk medicine must be herbal therapies as to build few adverse effects and reduce costly for alternative hyperglycemia agents. Particularly, curcumin (bis-α,β-unsaturated β-diketone), the chief constituent of turmeric plant (C. longa), plays a significant role in prevention of various diseases including diabetes by decrease blood glucose and increase plasma insulin level, [40] while different species has been taken as anti-diabetic agents in potent and safety on therapy of patient's diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional Arabic medicine is still practiced and may provide effective new compounds for treating diabetes and other diseases, as the 69 plant species that are reported in a review concerning diabetes treatment in Jordan (11). Some of these plants have been demonstrated to inhibit amylase and glucosidase activities in vitro and in vivo, including Geranium graveolens and Varthemia iphionoides (31), Pistacia atlantica, Rheum ribes and Sarcopoterium spinosum (32).…”
Section: Antidiabetic Plants Used In Traditional Medicinementioning
confidence: 99%
“…In this sense, herbal compounds appear to offer gentler means of managing metabolic disorders and, since ancient times, have been used in traditional medicine systems like Chinese, Indian ayurveda and Arabic unani (10). Therefore, evidence for a putative beneficial effect of a wide range of medicinal plants exists in relation to type 2 diabetes therapy (11). In addition to their effectiveness, herbal remedies seem to produce hardly adverse effects and present an economical alternative to the oral synthetic hypoglycemic agents.…”
Section: Introductionmentioning
confidence: 99%
“…The main active secondary metabolite in olive leaf extract is oleuropeinas in Fig. 1 (8). Studies have reported various pharmacological benefits of oleuropein.…”
Section: Introductionmentioning
confidence: 99%